Subpicosecond resonance Raman spectra of the early intermediates in the photocycle of bacteriorhodopsin - van den Berg, R. (1990)
The resonance Raman spectra are presented for the species formed during the photocycle of bacteriorhodopsin (bR) on a timescale of 800-900 fs. In the ethylenic stretch region two intermediates were found with frequencies of 1,510 and 1,518 cm(-1), corresponding to species with optical absorption maxima at 660 and 625 nm, respectively. This leads to the assignment of the 1,518 cm(-1) band to the J(625) intermediate. In the fingerprint region, the appearance of a vibration at 1,195 cm(-1) strongly suggests that the isomerization indeed has taken place in a time less than the pulsewidth of our laser. This supports the previous proposals made on the basis of the optical spectra. The spectra are compared with those observed in tens of picoseconds up to nanoseconds.